1978
DOI: 10.1172/jci108972
|View full text |Cite
|
Sign up to set email alerts
|

The effect of altered sodium balance upon renal vascular reactivity to angiotensin II and norepinephrine in the dog. Mechanism of variation in angiotensin responses.

Abstract: A B S T R A C T The mechanism whereby the vasoconstrictor response to angiotensin II (A,,) is influenced by sodium balance or disease is unclear. To explore this question, the renal vascular responses (RVR) to intrarenal injections of subpressor doses of A,, and norepinephrine were studied in dogs with an electromagnetic flowmeter. Acute and chronic sodium depletion increased plasma renin activity (PRA) and blunted the RVR to A,,, while acute sodium repletion and chronic sodium excess plus desoxycorticosterone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
1

Year Published

1979
1979
1985
1985

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 43 publications
(75 reference statements)
1
21
1
Order By: Relevance
“…The absence ofrenal vasoconstriction during the acute reduction of cardiac output is noteworthy because arterial plasma renin activity and arterial plasma concentration of norepinephrine were markedly elevated in response to thoracic caval obstruction (Tables III and IV) and because angiotensin II and norepinephrine are both renal vasoconstrictors (15). During acute heart failure, the renal venous renin activity and renal venous plasma norepinephrine concentration increased above control values.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The absence ofrenal vasoconstriction during the acute reduction of cardiac output is noteworthy because arterial plasma renin activity and arterial plasma concentration of norepinephrine were markedly elevated in response to thoracic caval obstruction (Tables III and IV) and because angiotensin II and norepinephrine are both renal vasoconstrictors (15). During acute heart failure, the renal venous renin activity and renal venous plasma norepinephrine concentration increased above control values.…”
Section: Resultsmentioning
confidence: 96%
“…Renal prostaglandin synthesis is increased in sodium depletion (30), hemorrhagic hypotension (31), renal artery constriction (31), and cirrhosis with ascitis (33). In all these conditions, administration of inhibitors of prostaglandin synthesis reduces renal blood flow (12,15,16,31). The mechanism(s) whereby the prostaglandins attenuate renal vasoconstrictor mechanisms remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lowering endogenous All levels with acute volume repletion (Oliver & Cannon, 1978) also enhanced the pressor response to All in rats with a low sodium intake. These results are consistent with the postulate that elevations in endogenous angiotensin II levels result in an attenuated response to this peptide as has been reported previously (Thurston & Laragh, 1975;Oliver & Cannon, 1978;Smyth & Fung, 1984). These results substantiated the sensitivity of our system for detecting differences in pressor responsiveness.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have demonstrated that changes in angiotensin II receptor occupancy, following alterations in endogenous angiotensin II concentrations, were responsible for changes in response to this peptide (Thurston & Laragh, 1975;Oliver & Cannon, 1978). Thus, reduction of endogenous angiotensin II levels either by increased sodium intake (Reid & Laragh, 1965;Slack & Ledingham, 1976), converting enzyme inhibition (Thurston & Laragh, 1975), bilateral nephrectomy (Swales et al, 1975) or prostaglandin synthetase inhibition (Smyth & Fung, 1984) would be expected to enhance the pressor responsiveness to exogenously administered angiotensin.…”
Section: Introductionmentioning
confidence: 99%